The implications of neutrino masses and models for neutrino masses - Tay, Fu Yang (2018)
Massive neutrinos have been widely studied for the past twenty years as the understanding of neutrino masses serves as a probe into the new physics beyond Standard Model. SM and MSSM models are shortly reviewed in this thesis as they are the prerequisite knowledge for the massive neutrino model. The discussions of massive neutrino are mainly separated into four sections. The nature of neutrino masses are discussed as the neutrinos are still undetermined whether they are Dirac or Majorana particles. The significant implication of massive neutrinos, neutrino oscillations and consequences in measurements of atmospheric and solar neutrinos are investigated. The latest measurements of neutrino mixing angles showed that the neutrino mixing pattern is deviated from the TB mixing pattern. Hence two neutrino sum rules which may be the ways to deviate the TB mixing pattern are introduced in this thesis. Three mass hierarchies of neutrinos which are given by the latest measurements are also discussed. Furthermore, several types of seesaw mechanisms are studied as they are commonly used in most models to induce the neutrino masses. The models of massive neutrinos are introduced. For instance, left-right symmetry, SUSY and GUT models. Finally, a SUSY SO(10) model with discrete family symmetry is briefly studied.